Human‐induced pluripotent stem cell‐derived cardiomyocytes: Cardiovascular properties and metabolism and pharmacokinetics of deuterated mexiletine analogs. Issue 4 (29th July 2021) - Gomez‐Galeno, Jorge; Okolotowicz, Karl; Johnson, Mark; McKeithan, Wesley L.; Mercola, Mark; Cashman, John R.
Abstract: Prolongation of the cardiac action potential (AP) and early after depolarizations (EADs) are electrical anomalies of cardiomyocytes that can lead to lethal arrhythmias and are potential liabilities for existing drugs and drug candidates in development. For example, long QT syndrome‐3 (LQTS3) is caused by mutations in the Nav 1.5 sodium channel that debilitate channel inactivation and cause arrhythmias. We tested the hypothesis that a useful drug (i.e., mexiletine) with potential liabilities (i.e., potassium channel inhibition and adverse reactions) could be re‐engineered by dynamic medicinal chemistry to afford a new drug candidate with greater efficacy and less toxicity. Human cardiomyocytes were generated from LQTS3 patient‐derived induced pluripotent stem cells (hIPSCs) and normal hIPSCs to determine beneficial (on‐target) and detrimental effects (off‐target) of mexiletine and synthetic analogs, respectively. The approach combined "drug discovery" and "hit to lead" refinement and showed that iterations of medicinal chemistry and physiological testing afforded optimized compound 22 . Compared to mexiletine, compound 22 showed a 1.85‐fold greater AUC and no detectable CNS toxicity at 100 mg/kg. In vitro hepatic metabolism studies showed that 22 was metabolized via cytochrome P‐450, as previously shown, and by the flavin‐containing monooxygenase (FMO). Deuterated‐22 showed decreased metabolism and showed acceptable cardiovascular and physicochemical properties. Abstract : Scheme for identification of Lead compounds.